The influence of hydrogen-ion concentration on the production of intermediate compounds in degradation reaction of D-giucose - Руденко, В. М. (Problems of Environmental Biotechnology, 2018)
In the paper there is considered the question of the influence of hydrogen-ions concentration on the formation of intermediates (unsaturated carbonyl-containing compounds with Lambdamax225 nm and carbonyl-containing compounds with Lambdamax285 nm) of the early stages of degradation D-glucose in aqueous solutions in pH range 1,0–7,0. By UV-spectroscopy there is demonstrated that an increase in hydrogen-ions concentration slows the formation of basic intermediates of the early stages, but it accelerates the transformation of unsaturated carbonyl-containing intermediates (Lambdamax225 nm) to 5-hydroxymethylfurfural. It was shown that reactions of the formation of unsaturated carbonyl-containing compounds, as starting intermediates for further transformations, slowed down at pH 3, indicating a certain stability of D-glucose under these conditions.